2010
DOI: 10.1093/deafed/enq019
|View full text |Cite
|
Sign up to set email alerts
|

Children With Cochlear Implants in Australia: Educational Settings, Supports, and Outcomes

Abstract: This Australian study examined the communication, academic, and social outcomes of pediatric cochlear implantation from the perspectives of teachers working with children with cochlear implants. The children were aged from 1 to 18 years and attended a range of educational settings in early intervention, primary, and secondary schooling. One hundred and fifty-one teachers completed a survey on one child with a cochlear implant and 15 of these teachers were interviewed. Teachers reported their perceptions of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 39 publications
3
37
1
5
Order By: Relevance
“…Similar to the results obtained in this study, Punch and Hyde (2010) observed that the vast majority of teachers who gave their opinion on the adaptive skills of these children, considered themselves to be in agreement with the idea that the implanted students had developed the social skills in accordance to their age. The studies by De Giacomo et al, (2013) andMartin, et al (2010) stated that there were no significant differences in the development of prosocial conducts between the implanted students and their hearing peers.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Similar to the results obtained in this study, Punch and Hyde (2010) observed that the vast majority of teachers who gave their opinion on the adaptive skills of these children, considered themselves to be in agreement with the idea that the implanted students had developed the social skills in accordance to their age. The studies by De Giacomo et al, (2013) andMartin, et al (2010) stated that there were no significant differences in the development of prosocial conducts between the implanted students and their hearing peers.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, in matters related to group play, results similar to those obtained by Punch and Hyde (2010) were observed, where at least 64% of classroom teachers agreed that implanted students participated regularly with their teammates in group play. These results fell significantly when the classroom teachers assessed (rating as Certainly True) the acceptance of implanted students in the classroom reaching 46.7% for classroom teachers and 56.7% for SLH teachers.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations